Analysis of Mathematic Connection Ability of Junior High School Students Class VII on Integer Numbers - Dila Anggaraini; Afra Rahmaulydina (Journal of Research on Mathematics Instruction (JRMI), 2021)
The research conducted aims to examine the ability in mathematical connections possessed by Junior High School Class VII students through integer material. The instrument in this study was in the form of a test of mathematical connection ability with as many as six essay questions. The study uses a qualitative approach with a descriptive method of technical data analysis. The results of the study obtained that the test results score from mathematical connection ability are three students with the high ability with a percentage of 15%, there are 13 students with medium category with a percentage of 65%, and there are four students with the low ability with a percentage of 20%.